Device-Related Thrombus After Left Atrial Appendage Closure: Data on Thrombus Characteristics, Treatment Strategies, and Clinical Outcomes From the EUROC-DRT-Registry. (19th May 2021) - Sedaghat, Alexander; Vij, Vivian; Al-Kassou, Baravan; Gloekler, Steffen; Galea, Roberto; Fürholz, Monika; Meier, Bernhard; Valgimigli, Marco; O'Hara, Gilles; Arzamendi, Dabit; Agudelo, Victor; Asmarats, Lluis; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Left atrial appendage closure is an established therapy in patients with atrial fibrillation. Although device-related thrombosis (DRT) is relatively rare, it is potentially linked to adverse events. As data on DRT characteristics, outcome, and treatment regimen are scarce, we aimed to assess these questions in a multicenter approach. Methods: One hundred fifty-six patients with the diagnosis of DRT after left atrial appendage closure were included in the multinational EUROC-DRT registry. Baseline characteristics included clinical and echocardiographic data. After inclusion, all patients underwent further clinical and echocardiographic follow-up to assess DRT dynamics, treatment success, and outcome. Results: DRT was detected after a median of 93 days (interquartile range, 54–161 days) with 17.9% being detected >6 months after left atrial appendage closure. Patients with DRT were at high ischemic and bleeding risk (CHA2 DS2 -VASc 4.5±1.7, HAS-BLED 3.3±1.2) and had nonparoxysmal atrial fibrillation (67.3%), previous stroke (53.8%), and spontaneous echo contrast (50.6%). The initial treatment regimens showed comparable resolution rates (antiplatelet monotherapy: 57.1%, dual antiplatelet therapy: 85.7%, vitamin K antagonists: 80.0%, novel oral anticoagulants: 75.0%, and heparin: 68.6%). After intensification or switch of treatment, complete DRT resolution was achieved in 79.5% of patients. Two-year follow-up revealed a high risk of mortality (20.0%) and ischemic stroke (13.8%) in patients with DRT. Patients with incomplete DRT resolution showed numerically higher stroke rates and increased mortality rates (stroke: 17.6% versus 12.3%, P =0.29; mortality: 31.3% versus 13.1%, P =0.05). Conclusions: A substantial proportion of DRT is detected >6 months after left atrial appendage closure, highlighting the need for imaging follow-up. Patients with DRT appear to be at a high risk for stroke and mortality. While DRT resolution was achieved in most patients, incomplete DRT resolution appeared to identify patients at even higher risk. Optimal DRT diagnostic criteria and treatment regimens are warranted.